2018
DOI: 10.2134/jeq2017.05.0214
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Eutrophication Is Reflected in the Stable Isotopic Composition of the Eastern Mudsnail, Nassarius obsoletus

Abstract: In aquatic ecosystems, biological indicators are used in concert with nutrient concentration data to identify habitat impairments related to cultural eutrophication. This approach has been less commonly implemented in coastal areas due to the dominance of physical conditions in structuring biological assemblage data. Here, we describe the use of the stable isotopic composition of (Say), the eastern mudsnail, as an indicator of cultural eutrophication for 40 locations in coastal estuaries in New York. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…δ 13 C is typically used to determine the origin of carbon sources 28 . δ 15 N values allow the study of trophic levels of consumers 28 , and the enriched nitrogen isotopic composition of biota can be an indicator of anthropogenic wastewater 27,29 . However, nutrient contamination studies that include multiple taxa and different trophic levels in the food webs are not common 30 .…”
Section: Introductionmentioning
confidence: 99%
“…δ 13 C is typically used to determine the origin of carbon sources 28 . δ 15 N values allow the study of trophic levels of consumers 28 , and the enriched nitrogen isotopic composition of biota can be an indicator of anthropogenic wastewater 27,29 . However, nutrient contamination studies that include multiple taxa and different trophic levels in the food webs are not common 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, spatial patterns showed that expression of eutrophication is enhanced behind tidal restrictions (Hughes et al, 2011). While these studies raised concerns about symptoms of eutrophication, biological assimilation can mask the detection of elevated N inputs by monitoring programs (Watson et al, 2017;Jeppesen et al, 2018;Sańchez et al, 2023). Datasets of multiple monitoring parameters including dissolved and sediment nutrients, oxygen and pH, phytoplankton and microalgal abundance each provide useful information for managers when setting goals for N reduction but are limited by their 30-year timescale.…”
Section: Potential Of Historical Isoscapes For Regulatory Policymentioning
confidence: 99%
“…Because coastal systems are changing over long periods of time, with shifting nutrient inputs, warming waters, and other effects of climate change, researchers have developed and refined methods to measure the δ 15 N values of shell-bound organic material, allowing them to glean information about historical N sources and sinks from archival samples [ 28 30 ]. These values serve as a record of δ 15 N of suspended particulate matter (SPM) [ 31 , 32 ] and provide information about N sources to the mollusk which reflect local nutrient processing [ 33 ]. Shells from museum collections, archives, and excavations from dated middens allow us to develop timelines of N sources and cycling that extend back thousands of years [ 22 , 31 ].…”
Section: Introductionmentioning
confidence: 99%